Open Reduction and Internal Fixation of a Partial Articular (OTA-43B) Pilon Fracture Through a Direct Anterior Approach. (August 2022) - Olszewski, Nathan; Tornetta, Paul
Summary: We present the management of an OTA-43B Pilon fracture with a depressed plafond fragment, medial comminution, and displacement of the Chaput fragment. The patient was initially managed with external fixation to gain initial reduction of the pilon fracture and to allow the soft tissues to heal. As demonstrated, the extensile anterior approach can be modified and used to see the anteromedial and anterolateral tibial plafond so an anatomic reduction could be obtained. Also detailed is the reduction and fixation strategy and soft tissue closure, all of which plays a critical role in the outcome.